An immunoinformatics-based designed multi-epitope candidate vaccine (mpme-VAC/STV-1) against Mycoplasma pneumoniae. (March 2022) - Vilela Rodrigues, Thaís Cristina; Jaiswal, Arun Kumar; Lemes, Marcela Rezende; da Silva, Marcos Vinícius; Sales-Campos, Helioswilton; Alcântara, Luiz Carlos Júnior; Tosta, Sthephane Fraga de Oliveira; Kato, Rodrigo Bentes; Alzahrani, Khalid J.; Barh, Debmalya; Azevedo, Vasco Ariston de Carvalho; Tiwari, Sandeep; et al.
Abstract: Pneumonia is a serious global health problem that accounts for over one million deaths annually. Among the main microorganisms causing pneumonia, Mycoplasma pneumoniae is one of the most common ones for which a vaccine is immediately required. In this context, a multi-epitope vaccine against this pathogen could be the best option that can induce effective immune response avoiding any serious adverse reactions. In this study, using an immunoinformatics approach we have designed a multi-epitope vaccine (mpme-VAC/STV-1) against M. pneumoniae . Our designed mpme-VAC/STV-1 is constructed using CTL (cytotoxic T lymphocyte), HTL (Helper T lymphocyte), and B-cell epitopes. These epitopes are selected from the core proteins of 88 M. pneumoniae genomes that were previously identified through reverse vaccinology approaches. The epitopes were filtered according to their immunogenicity, population coverage, and several other criteria. Sixteen CTL/B- and thirteen HTL/B- epitopes that belong to 5 core proteins were combined together through peptide linkers to develop the mpme-VAC/STV-1. The heat-labile enterotoxin from E. coli was used as an adjuvant. The designed mpme-VAC/STV-1 is predicted to be stable, non-toxic, non-allergenic, non-host homologous, and with required antigenic and immunogenic properties. Docking and molecular dynamic simulation of mpme-VAC/STV-1 shows that it can stimulate TLR2 pathway mediated immunogenic reactions. In silico cloning of mpme-VAC/STV-1 in an expression vector also shows positive results. Finally, the mpme-VAC/STV-1 also shows promising efficacy in immune simulation tests. Therefore, our constructed mpme-VAC/STV-1 could be a safe and effective multi-epitope vaccine for immunization against pneumonia. However, it requires further experimental and clinical validations. Highlights: M. pneumonia is responsible for community-acquired pneumonia worldwide. We have designed mpme-VAC/STV-1 multi-epitope candidate vaccine, using an immunoinformatics approach against M. pneumonia . In silico validations suggest mpme-VAC/STV-1 could be a strong vaccine candidate against M. pneumoniae infection. We are currently working on in vitro and in vivo validations of mpme-VAC/STV-1.